Th e clinical-economic analysis of Dupilumab in severe asthma - I. S. Krysanov; V. S. Krysanova; V. Yu. Ermakova (Izdatelstvo OKI, 2021)
Background. Severe Asthma is a most social important chronic illness due to highest expenditures of Health Care System for control and treatment of exacerbations and decreasing of GDP. Situation with modern treatment is better now because biologic drugs have introduced into real practice. Biologic drugs - dupilumab, mepolizumab, reslizumab and benralizumab - decrease annual exacerbation rate of severe asthma as well as improve a lung function. Comparison of clinical-economic analyses of biologic drugs usage can help choose an optimal treatment technology of severe asthma. Materials and methods. Calculation of direct and indirect costs of treatment based of indirect treatment comparison of biologic drugs in severe asthma has been performed. Weighted average annual number of exacerbations prevention was chosen as efficacy criteria and their were for dupilumab 200 mg - 0,41, 0,26 for mepolizumab, 0,22 for reslizumab, 0,16 - for benralizumab. Cost-effective ratios were calculated, and sensitivity analysis has been performed for results confirmation. Results. Direct annual costs were less for dupilumab treatment - 834 970 RUR/ patient/year. Same costs for others biologicals were: for mepolizumab - 935 931 RUR, for reslizumab - 1 582 577 RUR/patient/ year, for benralizumab - 1 224 786 RUR/patient/year. Dupilumab has demonstrated less indirect costs in severe asthma patients. Disability is a major contributor of GDP loss. Total expenditures were higher in mepolizumab (on 11,3 %), in reslizumab (on 82,9 %), in benralizumab (on 43,4 %) in compare with the same parameter for dupilumab. Sensitivity analysis has confirmed a stability results calculated in different scenariois. Conclusion. Dupilumab 200 mg in severe asthma is an preference alternative in the treatment compare with other biologics because it has better efficacy and less annual costs.